Synthesis of Zinc Sulfide Nanoparticles by Chemical Coprecipitation Method and its Bactericidal Activity Application - Razhan S. Othman; Rebaz A. Omar; Karzan A. Omar; Aqeel I. Gheni; Rekar Q. Ahmad; Sheyma M. Salih; Avan N. Hassan (Polytechnic)
A particle of zinc sulfide (ZnS) was synthesized by the chemical coprecipitation method using zinc sulfate heptahydrate (ZnSO4), ammonium sulfate (NH4) 2SO4 as a reactant, and thiourea as a stabilizer and capping agent. The optioned product characterized by electron dispersive X-ray spectroscopy that exhibits the presence of Zn and S elements. The average particle size of the ZnS nanoparticles determined using X-ray diffraction is about 4.9 nm. The ultraviolet–visible spectroscopy showed the blue shift in wavelength and the band gap was 4.33 eV, the surface morphology of the synthesized ZnS nanoparticles powder was studied by scan electron microscopy which was showed the irregular and some spherical shapes of ZnS in a nanosized range. The Fourier-transform infrared spectroscopy observed an absorption peck at 657.73 and 613.36 cm−1 that were assigned to the stretching mods of the Zn-S band. The different amounts of ZnS nanoparticle were applied as bactericidal against Staphylococcus aureus by disk diffusion method. It displayed activity against S. aureus bacteria, which was carried out in the absence of irradiation.